The safety of physically separated cycle tracks compared to marked cycle lanes and mixed traffic conditions in Amsterdam - van Petegem, Jan Hendrik; Schepers, Paul; Wijlhuizen, Gert Jan (European Journal of Transport and Infrastructure Research, 2021)
Bicycle infrastructure is utilised to improve cycling safety and encourage bicycle use as a sustainable and healthy transport mode. This study sets out to assess whether providing physically separated cycle tracks along distributor roads, as prescribed in Dutch design guidelines and the Sustainable Safety vision, yields the expected safety benefits for cyclists. Therefore the safety of physically separated cycle tracks is compared to marked or painted cycle lanes and to mixed traffic conditions at distributor roads with a speed limit of 50 km/h in Amsterdam in the Netherlands. The study also includes the presence of the risk factors curbside parking and trams. Since police records are known to underreport single bicycle crashes and other crashes without a motor vehicle involved, ambulance records are used in this study instead. Also, both motor vehicle volumes as well as cyclists counts are taken into account in the crash analysis. By doing so, this study aims to address two weaknesses of previous research, i.e. the lack of control for exposure of cyclists and the use of police recorded crashes which miss the majority of bicycle crashes without motor vehicles. Results show that, controlled for kilometres travelled by bicycle and by motor vehicle, 50-60% less bicycle crashes occur on distributor roads with cycle tracks compared to those with cycle lanes. Curbside parking and trams are related to an increased likelihood of bicycle crashes, a difference of a factor 2 and 1.7-2 respectively. The authors therefore recommend to favour physically separated cycle tracks over cycle lanes and to take out curbside parking from the cross section as this presents the possibility to introduce cycle tracks in existing cross sections and mitigate an important risk factor concurrently.